ANALISIS SINEMATOGRAFI FILM DOKUMENTER ”NEGERI DI BAWAH KABUT” - Helpia, Fira; Mukhlizar (Fakultas Agama Islam Universitas Muhammadiyah Bengkulu, 2024)
Cinematographyis an important aspect in the world of cinema. Good cinematography is able to convey the message of a film to the audience. The purpose of this research is to analyze the cinematography in the documentary film Negeri under the Mist, this can be seen from the main factors in conveying messages in a film using cinematography, thereby adding insight about the film. This research is a type of qualitative research with data collection, namely analysis of media texts, documentation and literature or library research by taking pictures or the remains of the author to obtain direct data which includes books, journals, documentary film articles and other data. The method used in this study is the Joseph V. Mascelli method.Based on the research results, this film uses the right cinematographic elements, as seen from the techniques used which have their own purpose and meaning, thereby beautifying the appearance of the documentary film. There are three angles that can be examined in the film Negeri di Bawah Fog using the Joseph V Mascelli method, namely the Eye level, Low angle and High angle techniques. Keywords: Cinematography, Dokumentary Film, “Negeri di Bawah Kabut”